PENDATAAN DAN PENDAMPINGAN PEMANFAATAN TEKNOLOGI UMKM DI KELURAHAN BESUSU BARAT KOTA PALU - Meity Ferdiana Paskual; Fastabikul Khoirot (JOURNAL OF COMMUNITY DEDICATION, 2025)
This community service activity aims to collect data from Micro, Small, and Medium Enterprises (UMKM) in Besusu Barat Village, Palu City, as an archive for the local government and provide technology assistance to UMKM actors in utilizing digital platforms. The methods used include initial discussions with the village government, mapping of UMKM locations, direct data collection, and training on online marketing through social media and e-commerce platforms. The results show that most UMKM actors have significant potential but still rely on offline marketing methods. Some UMKM actors who have adopted online marketing reported an increase in revenue of up to 40%. However, challenges such as the refusal of some UMKM actors to be recorded and limited internet access hinder the adoption of digital technology. Recommendations for future activities include increasing outreach on the importance of data collection, providing advanced training on digital technology, and facilitating UMKM actors with better internet infrastructure.